The Value of Women’s Capital in Management: The Polish Perspective - Szlachcic, Aleksandra (Wartość kapitału kobiet w zarządzaniu. Perspektywa Polski, 2025)
Aim: The aim of this paper is to demonstrate the value of women’s capital as a strategic asset in management and to trace the evolving attitudes toward gender equality in Poland over time. Methodology: The study is based on a case study of the magazine Forbes Women Polska, an individual in-depth interview with an expert from the field, and an analysis of the Gender Equality Index (GEI) covering the years 2013–2024. This methodological triangulation ensures a comprehensive perspective on the issue. Results: The findings highlight the significant benefits of maintaining gender equality in managerial positions, not only from an ethical perspective but also in terms of measurable advantages for firms and society. The study also reveals a gradual shift in public perceptions of gender roles in Poland, indicating increasing support for inclusive leadership. Implications and recommendations: The paper suggests that prioritising gender equality is a strategic imperative for organizations aiming to unlock human potential, stimulate innovation, and ensure sustainable growth. Further research should continue to explore the socio-economic outcomes of gender-inclusive management practices. Originality/value: This study provides a multidimensional insight into gender equality in Polish management through the integration of qualitative and quantitative methods. It offers evidence-based support for viewing women’s capital as a key contributor to organizational and societal development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 1, s. 95-108
Keywords: gender equality; management; project management; Forbes Women Polska; równość płci; zarządzanie; zarządzanie projektami